The effectiveness of motivational interviewing among dentists. systematic review - Ivashkina, O. A.; Makeeva, M. K. (Ėndodontii͡a︡ today = Endodontics today, 2023)
Aim . 1) To study the development of emotional burnout syndrome among dentists of different genders, ages, seniority and place of work, and different specializations. 2) Analyze the effectiveness of motivational interviewing (MI) among dentists with symptoms of emotional burnout. 3) To study the influence of MI on the behavior and psycho-emotional state of dentists, on the development of emotional burnout syndrome, empathy and job satisfaction. Materials and Methods . Studying the relevance of "motivational interviewing" in PubMed and Web of Science databases. Evaluation of the effectiveness of MI in medical practice among dentists with symptoms of emotional burnout. Modification of the professional burnout questionnaire in accordance with the specifics of the professional duties of dentists and the manifestations of burnout. A questionnaire was conducted to determine the development of professional burnout syndrome among dentists. Results . In this study, we conducted a questionnaire among 135 dentists, taking as a sample the Questionnaire of emotional burnout K. Maslach and S. Jackson. Based on this model, the "Areas of Worklife Survey" and the "General Health Questionnaire" (General Health Questionnaire GHQ-12) were constructed and modified. The questionnaire showed that among dentists, pediatric dentists suffer from a large percentage of the development of burnout (75%), followed by dental therapists (65%), universal dentists (44%), dental surgeons (38%), orthopedic dentists (35%), dentists and orthodontists (30%). The presence of signs of burnout requires corrective action such as the method of motivational interviewing. We have developed methodological recommendations for individual training with the use of MI for dentists of various specialties with emotional burnout syndrome. The results of the study show that the percentage of dentists with burnout after training with MI becomes 3% less. Conclusions . Timely preventive and corrective measures reduce the negative impact of the burnout syndrome on the personality of a professional. Motivational interviewing is useful for strengthening motivation to change behavior in dentists working with patients who have various behavioral problems.